Емпіричне дослідження психологічного благополуччя поліціантів у період середньої дорослості - Резнік, К. О.; Reznik, K. O. (Вчені записки ТНУ імені В. І. Вернадського. Сер.: Психологія. – 2023. – Т. 34 (73), № 1. - С. 184-189, 2023)
Визначено особливості психологічного благополуччя у поліцейських середньої дорослості з урахуванням їх гендерних відмінностей. Емпірично доведено, що специфіка психологічного благополуччя у жінок й чоловіків поліцейських середнього періоду дорослості має значущі відмінності за показниками «Особистісній ріст», «Життєві цілі» та «Самоприйняття». Встановлено, що показники особистісного зростання та життєвих цілей вищі у групі чоловіків, ніж у жінок. Відзначено, що жінки виявляють вірогідні відмінності за показником «Самоприйняття», що свідчить про їх позитивне ставлення до себе, усвідомлення своїх сильних й слабких сторін. У поліціантів жінок та чоловіків середньої дорослості показники психологічного благополуччя майже за усіма компонентами показали середні бали. Результати отримані за інтегрованим показником психологічного благополуччя свідчать, що у чоловіків він є дещо вищим, ніж у групі жінок. Емпірично обґрунтовано, що психологічне благополуччя у чоловіків середньої дорослості демонструється через можливості отримати новий досвід, реалізувати свій потенціал, а у жінок характеризується бажанням залучити свої переваги у діяльність з метою досягнення успіху та відчутті впевненості у собі.

The article presents theoretical and empirical study of indicators of psychological well-being among police officers in the middle period of adulthood. The psychological analysis of the problem has a long history and includes a large number of works on this problem. Within our research, psychological well-being is interpreted as a complex integrative process, which is formed as a result of the symbiosis of various structural components. Science offers a sufficient number of approaches to the study of psychological well-being in the period of human maturity, however, in the practice of policing, an overview of this problem is insufficient. The purpose of the study is to reveal the peculiarities of psychological well-being in middle-aged policemen, taking into account their gender differences. The empirical basis of the study was 85 police officers. Groups were divided by gender and age. The first group included 32 female police officers in middle adulthood. The second group consisted of 53 male policemen in middle adulthood. The questionnaire "Express assessment of psychological well-being" by K. Riff, was involved in the study. It has been empirically proven that the specifics of psychological well-being of female and male police officers in the middle period of adulthood have significant differences according to the indicators "Personal Growth", "Purpose in Life" and "Self-Acceptance". It was established that the indicators of personal growth and life goals are higher in the group of men than in women. It was determined that women show probable differences according to the " Self-Acceptance" indicator, which indicates their positive attitude towards themselves, awareness of their strengths and weaknesses. The indicators of psychological well-being in almost all components of middle-aged male and female police officers showed average scores. The results obtained on the integrated indicator of psychological well-being indicate that it is slightly higher in men than in the group of women. It is empirically substantiated that psychological well-being in men in middle adulthood is demonstrated through opportunities to gain new experience, to realize their potential, and in women it is characterized by a desire to involve their advantages in activities in order to achieve success and a sense of self-confidence.

Определены особенности психологического благополучия у полицейских средней взрослости на основе их гендерных различий. Эмпирически доказано, что специфика психологического благополучия у женщин и мужчин полицейских среднего периода взрослости имеет значительные отличия по показателям «Личностный рост», «Жизненые цели» и «Самопринятие». Установлено, что показатели личностного роста и жизненных целей выше в группе мужчин, чем у женщин. Определено, что женщины проявляют вероятные отличия по показателю «Самопринятия», что свидетельствует об их положительном отношении к себе, осознании своих сильных и слабых сторон. У полицейских женщин и мужчин средней взрослости показатели психологического благополучия почти по всем компонентам показали средние баллы. Результаты полученные по интегрированному показателю психологического благополучия свидетельствуют, что у мужчин он несколько выше, чем в группе женщин. Эмпирически обосновано, что психологическое благополучие у мужчин средней взрослости демонстрируется через возможность получить новый опыт, реализовать свой потенциал, а у женщин характеризуется желанием привлечь свои преимущества в деятельность с целью достижения успеха и ощущения уверенности в себе.
Empirical study of the features psychological well-being of police officers in the period of middle adulthood
Резнік, К. О.Емпіричне дослідження психологічного благополуччя поліціантів у період середньої дорослості / Резнік К. О. // Вчені записки ТНУ імені В. І. Вернадського. Сер.: Психологія. – 2023. – Т. 34 (73), № 1. - С. 184-189. - DOI: https://doi.org/10.32782/2709-3093/2023.1/30.
Keywords: Психологія. Рsychology. Психология; Юридична психологія. Legal psychology. Юридическая психология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; поліцейські; police officers; полицейские; період середньої дорослості; period of middle adulthood; период средней взрослости; психологічне благополуччя; psychological well-being; психологическое благополучие; чоловіки; men; мужчины; жінки; women; женщины; гендерні особливості; gender characteristics; гендерные особенности